2022
DOI: 10.1097/md.0000000000028890
|View full text |Cite
|
Sign up to set email alerts
|

Educational suitability of new channel-type video-laryngoscope with AI-based glottis guidance system for novices wearing personal-protective-equipment

Abstract: The aim of this study was to determine which of 4 laryngoscopes, including A-LRYNGO, a newly developed channel-type videolaryngoscope with an embedded artificial intelligence-based glottis guidance system, is appropriate for tracheal intubation training in novice medical students wearing personal protective equipment (PPE).Thirty healthy senior medical school student volunteers were recruited. The participants underwent 2 tests with 4 laryngoscopes: Macintosh, McGrath, Pentax Airway-Scope and A-LRYNGO. The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…10 But a cohort study in 2022 reported that patient with category hard to ventilate and hard to intubate with LEMON score >4 has higher failure risk in first attempt intubation. 11 In this patient, endotracheal intubation was successfully performed after second attempt with limited laryngeal view Cormack-Lehane class 3.…”
Section: Discussionmentioning
confidence: 80%
“…10 But a cohort study in 2022 reported that patient with category hard to ventilate and hard to intubate with LEMON score >4 has higher failure risk in first attempt intubation. 11 In this patient, endotracheal intubation was successfully performed after second attempt with limited laryngeal view Cormack-Lehane class 3.…”
Section: Discussionmentioning
confidence: 80%
“…Anesthesiologists who take an active role in aerosolgenerating procedures such as endotracheal intubation are six times more at risk of coronavirus infection than other healthcare workers [5]. In patients infected with Covid-19, using a video laryngoscope as an alternative to direct laryngoscopy is recommended to protect the intubator from infection and reduce intubation failure due to personal protective equipment worn to prevent exposure to infection [4]. Also, aerosol cans used to reduce the risk of Covid-19 transmission during intubation may make it difficult to maneuver the laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 10% of healthcare workers who perform endotracheal intubation on patients with suspected or confirmed Covid-19 are reported to be infected with Covid-19 [3]. In patients infected with Covid-19, the use of video laryngoscopes instead of direct laryngoscopy is recommended to protect the intubator from infection and to reduce intubation failure due to personal protective equipment worn to prevent exposure to infection [4]. However, the cost of video laryngoscopes limits their availability in all health institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Some deep learning algorithms can identify vital anatomical structures, such as blood vessels, faster and more accurately than human experts. Such capabilities can elevate the speed and precision of diagnoses ( 35 , 46 ). Furthermore, AI can aid physicians in diagnosing complex diseases based on a broader array of symptoms ( 41 , 44 ), such as arteriosclerosis and fractures.…”
Section: Bibliographic Analysis Of Emergency Department Ai Opportunit...mentioning
confidence: 99%